Temporal considerations in contact lens discomfort. Issue 1 (February 2021) - Papas, Eric B.; Chiem, Annie; Zhang, George; Mobeen, Rabia; Lee, Ling
Abstract: Purpose: To determine the relative contributions to perceived discomfort during contact lens wear of contact time with the lens and the time of day at which wear begins, using a wearing framework similar to that of regular users. Methods: Twenty-three participants reported ocular discomfort using a 1–100 visual analogue rating scale, when prompted by email, during one day without contact lenses and on three other days while wearing soft contact lenses for twelve hours. Contact lens wear began at a different time on each day. The effect of start time on the change in discomfort during the wearing period was evaluated. Results: The average (± 95 % CI) change in discomfort over 12 h without contact lenses was -0.3 ± 3.5. The corresponding values during contact lens wear were 23.5 ± 14.6 when starting wear before 8am, 16.8 ± 11.0 when starting between 8am & 10am and 22.7 ± 8.4 when starting after 10am. While the increased discomfort was significant irrespective of start time (p < 0.01), there were no statistically significant differences between start times (p = 0.98). Conclusion: Discomfort during contact lens wear is associated with the length of time lenses are on-eye but not with the time of day when lenses are placed on-eye. This relationship is variable in the population and does not, of itself, explain why contact lenses become uncomfortable during wear. Active monitoring of participant compliance should be a consideration in all studies involving time critical responses.